2015
DOI: 10.1074/jbc.m115.641332
|View full text |Cite|
|
Sign up to set email alerts
|

Wnt/β-Catenin Mediates AICAR Effect to Increase GATA3 Expression and Inhibit Adipogenesis

Abstract: Background: Adipogenesis can be modulated by various signaling pathways and transcription factors. Results: AICAR-activated AMPK inactivates GSK3␤, which stimulates Wnt/␤-catenin signaling and relieves CtBP repression, thus increasing GATA3 and inhibiting adipogenesis. Conclusion: AMPK controls the Wnt/␤-catenin/GATA3 axis via inactivating GSK3␤ to coordinately modulate adipogenesis. Significance: These findings provide new insight into the molecular mechanism and signal transduction of adipogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…S4). Therefore, we evaluated the correlation between AMPK and ECHS1, which has been previously reported to regulate GATA3 transcription (33) and whose level is decreased in ccRCC 3, as confirmed in this study by IHC ( Fig. 3D; Supplementary Fig.…”
Section: Ampk Regulates Echs1 Through Gata3supporting
confidence: 68%
“…S4). Therefore, we evaluated the correlation between AMPK and ECHS1, which has been previously reported to regulate GATA3 transcription (33) and whose level is decreased in ccRCC 3, as confirmed in this study by IHC ( Fig. 3D; Supplementary Fig.…”
Section: Ampk Regulates Echs1 Through Gata3supporting
confidence: 68%
“…β-catenin was a multifunctional protein which had the dual activity of mediating cell adhesion and signal transduction [ 29 , 30 ]. After accumulation in the nucleus, β-catenin would form a transcription factor complex with the transcription factor TCF/LEF through its C-terminal transcriptional activator binding site, thereby facilitating the transcription of downstream target genes such as CyclinDl and e-mys [ 31–33 ]. In the present study, we observed that FOXF2 could suppress the expression level of β-catenin in the nucleus and target genes expression in the Wnt/β-catenin signaling pathway, such as c-Myc, CyclinDl, MMP9, and Lgr5.…”
Section: Discussionmentioning
confidence: 99%
“…32) Moreover, there are several reports showing that direct pharmacological activation of AMPK inhibits adipogenesis. 33,34) Collectively, our results suggest that gallic acid is a major bioactive component in FPE, and it exerts potent anti-obesity effects in vivo and in vitro through AMPK activation. A couple of recent studies have also reported beneficial effects of gallic acid on high fat diet-induced obesity, but the underlying mechanisms including changes in genes expression involved in fatty acid synthesis are yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 66%